SEMIOTICS ANALYSIS OF THE MEANING OF MENTAL HEALTH MOTIVATION IN SONG LYRICS 00:00 ZERO O'CLOCK BY BTS - Diana Ayu Pratiwi; M.Yose Rizal Saragih (LP2M IAI Nazhatut Thullab Sampang, 2022)
Abstract: This study discusses the meaning of mental health motivation in the lyrics of the song Zero O'Clock. This study aims to focus on knowing how the meaning of mental health motivation is described in the lyrics of the song Zero O'Clock by BTS. To find out the representation of the meaning of mental health motivation in the song Zero O'Clock by BTS, the researchers used qualitative research methods. The data obtained were then analyzed using the semiotic approach of Roland Barthes' model by clarifying the terms in the lyrics of verse one to verse 4. The results showed that the song Zero O'Clock has the meaning of health motivation to entertain listeners and heal the mind according to their situation. At first everyone felt tired of their activities and felt left behind from others to the point of hating the world. However, at 00:00 is a new beginning, hopefully tomorrow will be happier and stop thinking about bad things. Pray and smile proudly for having a great day through a tough day. Keywords: Song Lyrics Representation, Mental Health Motivation, BTS